1981
DOI: 10.1148/radiology.139.3.7232730
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography in obstructive jaundice. Part II: The cause of obstruction.

Abstract: The value of computed tomography (CT) in determining the cause of obstructive jaundice in 67 proved cases is described. The presence of stones, the level of obstruction, the relative size of the ringlike structures produced by the dilated bile duct, and the shape of the distal visualized ring have proved to be the most important variables. The retrospective analysis determined the correct cause in 94% of the cases. CT fulfills all goals considered important in obstructive jaundice and eliminates the need for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…US revealed obstruction in 87% of these patients, although it demonstrated the cause of obstruction less frequently. Similar findings for the accuracy of CT and US have appeared in other recent reports [9][10][11][12]. In our series, CT was utilized in only 3 patients with surgically proven common duct stones.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…US revealed obstruction in 87% of these patients, although it demonstrated the cause of obstruction less frequently. Similar findings for the accuracy of CT and US have appeared in other recent reports [9][10][11][12]. In our series, CT was utilized in only 3 patients with surgically proven common duct stones.…”
Section: Discussionsupporting
confidence: 90%
“…The utility of US and CT in the diagnosis of surgical cholestasis is well-documented [6][7][8][9][10][11]. Baron et al demonstrated the value of US and CT in the diagnosis of biliary obstruction [6].…”
Section: Discussionmentioning
confidence: 99%
“…Reported CT sensitivity for CBDS ranges from 25-90% [55,[60][61][62]. PTC is accurate in detecting CBDS when the bile duct is opacified.…”
Section: Non-endoscopic Imaging Studiesmentioning
confidence: 99%
“…The sensitivity and predictive value of computed tomography in diagnosis of obstruction is comparable to that of usa and in addition it is more likely to yield clues regarding the level or the nature of the obstruction [13,14].…”
Section: Discussionmentioning
confidence: 95%